MODERN APPROACHES TO TEACHING IN THE FIELD OF ENGINEERING (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article explores the significance of engineering within various branches of industrial production, emphasizing its crucial role in ensuring efficiency, innovation, and sustainable development. It examines the professional functions and responsibilities of engineers in modern manufacturing environments, as well as the interdependence between fundamental (core) and specialized disciplines in engineering education. Particular attention is paid to contemporary pedagogical approaches aimed at enhancing the quality of engineering training, including competency-based education, project-oriented learning, digital modeling, and simulation technologies. The study highlights the relevance of integrating advanced technical knowledge with practical skills to meet the demands of rapidly evolving industrial sectors. Furthermore, the article outlines methodological principles, teaching strategies, and future prospects for improving engineering education to align with global technological and market trends.